ETIKA BISNIS DIVISI PEMASARAN DI PT. KC SOFTEX INDONESIA - Dini Yuniar Pratama (Jurnal Bina Bangsa Ekonomika, 2023)
Ethics is a person's behavior on good or bad things through a written or oral. While business is an individual or organizational activity that creates a product or service that intends to make a profit and to meet the needs of society. The author's goal in making this article is to provide information about business ethics at PT. KC Softex Iindonesia engaged in modern and traditional retail. The ethics that must be followed so that the business can be successful and run smoothly as desired, such as building a harmonious relationship between employees, superiors and consumers. This research method uses descriptive and normative analysis in order to obtain good and accurate information to understand the concept of business ethics at PT. KC Softex Indonesia